Scintillation-limited photometry with the 20-cm NGTS telescopes at Paranal Observatory. Issue 4 (26th November 2021) - O'Brien, Sean M; Bayliss, Daniel; Osborn, James; Bryant, Edward M; McCormac, James; Wheatley, Peter J; Acton, Jack S; Alves, Douglas R; Anderson, David R; Burleigh, Matthew R; Casewell, Sarah L; Gill, Samuel; et al.
ABSTRACT: Ground-based photometry of bright stars is expected to be limited by atmospheric scintillation, although in practice observations are often limited by other sources of systematic noise. We analyse 122 nights of bright star ( G mag ≲ 11.5) photometry using the 20-cm telescopes of the Next-Generation Transit Survey (NGTS) at the Paranal Observatory in Chile. We compare the noise properties to theoretical noise models and we demonstrate that NGTS photometry of bright stars is indeed limited by atmospheric scintillation. We determine a median scintillation coefficient at the Paranal Observatory of $C_{\scriptscriptstyle \text{Y}}= 1.54$, which is in good agreement with previous results derived from turbulence profiling measurements at the observatory. We find that separate NGTS telescopes make consistent measurements of scintillation when simultaneously monitoring the same field. Using contemporaneous meteorological data, we find that higher wind speeds at the tropopause correlate with a decrease in long-exposure ( t  = 10 s) scintillation. Hence, the winter months between June and August provide the best conditions for high-precision photometry of bright stars at the Paranal Observatory. This work demonstrates that NGTS photometric data, collected for searching for exoplanets, contains within it a record of the scintillation conditions at Paranal.